2010
DOI: 10.1002/jbt.20344
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring treatment response of childhood acute lymphocytic leukemia with certain molecular and biochemical markers

Abstract: Apoptosis is the primary mechanism through which most chemotherapeutic agents induce tumor cell death. The purpose of this study was to monitor the expression of pro- and anti-apoptotic proteins CD(95) , Bcl-2, as well as copper and zinc levels in the peripheral blood of children with acute lymphocytic leukemia (ALL) prior to and 6 months after the beginning of chemotherapy. Blood parameters and bone marrow blast count were also assessed. Twenty of 26 patients who received treatment showed amelioration in apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…On the other hand, Bax mRNA levels were found to be higher in the ALL group than in the Remission group (p = 0.001). These Bax mRNA results are consistent with the results of Barakat et al [15] and Maia et al [18]. We found no similar studies on Bad mRNA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, Bax mRNA levels were found to be higher in the ALL group than in the Remission group (p = 0.001). These Bax mRNA results are consistent with the results of Barakat et al [15] and Maia et al [18]. We found no similar studies on Bad mRNA.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed that both Bcl-2 and Bcl-xL mRNA levels were significant-ly higher in the ALL group than in the Remission group (p = 0.001). The Bcl-2 results were consistent with what was found by Barakat et al [15], and Hogarth et al [16]. The increase in Bcl-2 con- centration in newly diagnosed ALL cases was suggested to be due to DNA hypomethylation at the 5 end of the Bcl-2 gene.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…30 The analysis of complete blood count in ALL patients revealed the presence of leukocytosis, anemia, thrombocytopenia, and high blast percentage; these findings were consistent with the results of many studies in Sudan, Mexico, Iran, Egypt, and Pakistan. [31][32][33][34][35] In this study, B-ALL was more frequent than T-ALL; this outcome agrees with many studies conducted in Jordan, Brazil, Italy, Egypt, and Mexico; all of them reported higher frequency for B-ALL than T-ALL. 26,[36][37][38][39][40] On the other hand, our finding disagrees with two studies conducted in Iran and Pakistan; both found that the frequency of T-ALL is greater than B-ALL.…”
Section: Discussionsupporting
confidence: 90%